1994
DOI: 10.1136/gut.35.12.1747
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility and bulking effect of ispaghula husks in healthy humans.

Abstract: The digestibility of ispaghula, a mucilage from Plantago ovata composed mainly of arabinoxylans, and its faecal bulking effect were studied in seven healthy volunteers who ingested a low fibre controiled diet plus either placebo or 18 glday ofispaghula for two 15 day periods. Whole gut transit time and gas excretion in breath and flatus were not different during the periods of ispaghula and placebo ingestion. Faecal wet and dry weights rose significantly, however, during ispaghula ingestion. Faecal short chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 33 publications
8
74
1
1
Order By: Relevance
“…be at least partially resistant to fermentation and/or slowly fermented in the colon) and have a significant waterholding capacity. Faecal-bulking capacity of various dietary fibre sources has been measured and/or discussed by several authors (14)(15)(16)(17)(18) and it was concluded that there are few dietary fibre types which meet all these criteria. Monro (16) has developed a table of faecal bulking index of sixty-six foods along with their TDF content, but these were based on measurements in rats so may not be directly applicable to humans.…”
Section: Df = Nsp + Rs + Ro Mu ≥3mentioning
confidence: 99%
“…be at least partially resistant to fermentation and/or slowly fermented in the colon) and have a significant waterholding capacity. Faecal-bulking capacity of various dietary fibre sources has been measured and/or discussed by several authors (14)(15)(16)(17)(18) and it was concluded that there are few dietary fibre types which meet all these criteria. Monro (16) has developed a table of faecal bulking index of sixty-six foods along with their TDF content, but these were based on measurements in rats so may not be directly applicable to humans.…”
Section: Df = Nsp + Rs + Ro Mu ≥3mentioning
confidence: 99%
“…• faecal bulking or stool output (ispaghula, xanthan gum and wheat bran) (Daly et al 1993;Marteau et al 1994;Cummings, 1997); • lowering of postprandial blood glucose response (highly viscous guar gum or β-glucans) (Bourdon et al 1999); • lowering of plasma (LDL-) cholesterol (highly viscous guar gum, β-glucans or oat bran, pectins, psyllium) Anderson et al 2000;Jenkins et al 2002).…”
Section: Brief Presentation Of the Main Health Benefits Of Dietary Fibrementioning
confidence: 99%
“…It has been established that microbiota patterns differ between stomach, upper small bowel, lower small bowel and rectum in healthy adults (Flourie et al, 1986;Evans et al, 1988;Marteau et al, 1994;Evans, 1998). However, it is not known if surgical interruption of the developing intestinal ecosystem in the infant with an ileostomy results in modification of expected microbiota or adaptation of the neoterminal ileum to yield a microbiota pattern similar to that of the infant colon.…”
Section: Introductionmentioning
confidence: 99%